The work of a student to solve the equation 3(2x – 4) = 8 + 2x + 6 is shown below:
Step 1: 3(2x – 4) = 8 + 2x + 6
Step 2: 5x – 7 = 14 + 2x
Step 3: 5x – 2x = 14 + 7
Step 4: 3x = 21
Step 5: x = 7
In which step did the student first make an error and what is the correct step? (5 points)
Step 2; 6x – 12 = 14 + 2x
Step 2; 6x – 7 = 2(6 + x + 4)
Step 3; 5x – 2x = 14 – 7
Step 3; 5x + 2x = 14 + 7

Respuesta :

Neuron
If you would like to know in which step did the student first make an error and what is the correct step, you can calculate this using the following steps:

3(2x - 4) = 8 + 2x + 6
6x - 12 = 8 + 2x + 6
6x - 12 = 14 + 2x ... Step 2
6x - 2x = 14 + 12
4x = 26
x = 26/4 = 13/2

The correct result would be Step 2; 6x - 12 = 14 + 2x.

Answer:

id say step 2

Step-by-step explanation: